Is Rationalism Possible in the Muslim World? (American Journal of Islam and Society, 1999)
This article looks at the rationalist movement in the Muslim world inthe earlier centuries of Islam and discusses the reasons for its imtial successand later setback. The article then discusses the implications of thissetback for the revival of Islam and the ability of Muslim societies tomeet successfully the challenges that they face in modern times.